Co-exposure of sequential extreme weather and non-biodegradable/biodegradable microplastics (NBMPs/BMPs) on soil bacterial communities and the extracellular polymeric substances (EPS)-extracellular enzyme interaction mechanisms - Xinyu Yang; Yulian Ma; Xin Wang; Yue Sun; Qianzhi Zeng; Yunhong Pu; Bowen Yang; Yaxuan Wu; Xinran Su; Linna Shi; Shuang Li; Wenzhuo Sui; et al. (Journal of Environmental Chemical Engineering, 2026)

A novel perspective on the aging of raw Pu-erh tea: a comprehensive evaluation of the impact of different storage containers on flavor quality - Di Tian; Ting Wu; Linna Ma; Xiaohui Zhou; Chenyang Ma; Ning Chen; Haiyan Yi; Yapeng Liu; Yali Li; Yong-Quan Xu; Hongjie Zhou; Xiujuan Deng (Food Research International, 2026)

Phenothiazine-based self-assembled monolayer enabling high-efficiency and scalable inverted perovskite solar cells - Huilin Xie; Mingxin Wang; Xiaofeng He; Peng Wang; Miaoxin Li; Cheng Zhong; Qunliang Song; Yong Hua; Fei Wu; Linna Zhu (Chemical Engineering Journal, 2026)

Quaternized chitosan-coordinated metal-azolate framework: Core-bridge-shell composite for electrostatic flocculation and long-term Microcystis aeruginosa inhibition - Cai Cheng; Xuehan Xu; Yu Wu; Linna Shao; Jie Yu; Wenqi Zhang; Xianyong Kou; Xingyu Xiang; Yue Chen; Lingling Feng (Journal of Hazardous Materials, 2026)

Unraveling the alkali tolerance of microcystinase A within alkaline algal bloom scenarios - Wenqi Zhang; Linna Shao; Xingyu Xiang; Cai Cheng; Yu Wu; Xianyong Kou; Jie Yu; Ziqi Xiong; Xiaoliang Guo; Lingling Feng (Environmental Pollution, 2026)

DOM-mediated interaction of DOM-enzyme-pollutants affected the toxicity of combined aged tire wear particles (aged-TWPs) and polyfluoroalkyl substances (PFASs) in soil under successive extreme weather stress - Xin Wang; Yulian Ma; Xinyu Yang; Yue Sun; Wenzhuo Sui; Yunhong Pu; Qianzhi Zeng; Yaxuan Wu; Bowen Yang; Xinran Su; Shuang Li; Linna Shi; et al. (Journal of Environmental Management, 2026)

Effects of Perfluoroheptanoic Acid (PFHpA) on Bacterial Community, Elemental Cycling and ARGs Transmission in Sediment - Shengnan Shi; Xinran Su; Linna Shi; Shuang Li; Yunhong Pu; Qianzhi Zeng; Bowen Yang; Yaxuan Wu; Yue Sun; Yulian Ma; Xinyu Yang; Xin Wang; et al. (Water, Air, & Soil Pollution, 2026)

Enrichment mechanisms of rare earth elements associated with bauxite in northern Guizhou, China: An integrated study using microanalysis and machine learning - Shuhang Chen; Yong Fu; Feng Tian; Chuan Guo; Xinnian Li; Shuaichao Wei; Guodong Liu; Linna Wu (Journal of Asian Earth Sciences, 2026)

Corrigendum to “Straw return enhances nitrogen loss from groundwater in agricultural areas by triggering the switch from DNRA to denitrification”. [J. Hydrol. 662 (2025) 133818] - Han Wu; Linna Jia; Zhiyuan Zhang; Hang Fu; Rucai Ma; Jia Xin (Journal of Hydrology, 2026)

Distribution simulation and risk assessment of total phosphorus in mega-scale reservoir under different water diversion operations and upstream inflow scenarios: A case study in China - Xizhi Nong; Linna Wu; Siyuan Zhong; Lihua Chen; Jiahua Wei (Ecological Modelling, 2026)

Straw return enhances nitrogen loss from groundwater in agricultural areas by triggering the switch from DNRA to denitrification - Han Wu; Linna Jia; Zhiyuan Zhang; Hang Fu; Rucai Ma; Jia Xin (Journal of Hydrology, 2025)

Study on high-content screening-based allelopathic inhibition by Macleaya cordata extracts on Microcystis aeruginosa and its mechanism - Linna Shao; Shi Huang; Liexiong Zhang; Yu Wu; Cai Cheng; Xiaoliang Guo; Jie Yu; Xingyu Xiang; Wenqi Zhang; Xuehan Xu; Lingzi Zuo; Lingling Feng (Algal Research, 2025)

Quasi-pure-phase 2D perovskites for high-efficiency and stable 2D/3D perovskite heterojunction solar cells - Fei Wu; Yuping Gao; Ye Zeng; Junhong Tan; Cheng Zhong; Xing Gao; Yingguo Yang; Yongsheng Liu; Linna Zhu (Chemical Engineering Journal, 2025)

Efficient removal and action mode of low-cost zinc-based metal-azolate frameworks regulated by ligand on Microcystis aeruginosa - Cai Cheng; Jie Yu; Linna Shao; Yu Wu; Shi Huang; Liexiong Zhang; Xuehan Xu; Xingyu Xiang; Xiaoliang Guo; Lingling Feng (Chemical Engineering Journal, 2025)

Synergistic bioaugmentation: Serratia sp. WKD and carboxymethyl cellulose-modified nano-zero-valent iron enhance malachite green decolorization by activated sludge - Linna Du; Xinjiao Dong; Huan Wu; Gang Li; Jiacheng Zhou; Yiqing Wu; Yanping Xiao; Jing Qin; Xiu Wang (Journal of Water Process Engineering, 2025)

Efficient immobilization of CMlrA on mesoporous carriers for synchronized harmful Microcystis blooms suppression and microcystin degradation - Yu Wu; Linna Shao; Cai Cheng; Xianyong Kou; Shi Huang; Liexiong Zhang; Jie Yu; Xuehan Xu; Xingyu Xiang; Xiaoliang Guo; Lingling Feng (Journal of Hazardous Materials, 2025)

Advanced sequential treatment approach for enhanced recovery in tungsten-nickel electroplating wastewater - Shilong Lin; Bingzhi Yi; Xiangjun Hu; Linna Fang; Shuiyong Yu; Sanchuan Yu; Doufeng Wu (Journal of Water Process Engineering, 2025)

Dilute formic acid and alkaline oxidation relay treatment for the whole-fraction efficient gradient separation of space Arundo donax - Wenlong Xu; Xuanjie Zou; Ruotong Cui; Dameng Wang; Qilin Guo; Yanchao Shang; Jialin Zhao; Peijie Zong; Yifan Wu; Haozhe Zhang; Biao Liang; Linna Deng; et al. (Journal of Cleaner Production, 2025)

β-Cyclodextrin based magnetic hyper-crosslinked polymer: A recyclable adsorbent for effective preconcentration of triazine herbicides in complex sample matrices - Linna Guo; Qianqian Wang; Qiuhua Wu; Chun Wang; Baojiang Chen (Food Chemistry, 2025)

Niche-specific evolution and gene exchange of Salmonella in retail pork and chicken - Huanjing Sheng; Linna Zhao; Jia Suo; Qiuping Yang; Chenyang Cao; Jia Chen; Guangqing Cui; Yiling Fan; Yi Ma; Shengnan Huo; Xin Wu; Tao Yang; et al. (Food Research International, 2024)

Corrigendum to ‘Heavy metals and metalloids exposure and liver function in Chinese adults - A nationally representative cross-sectional study’ [Environ. Res. 252-P2 (2024) 118653] - Shiyu Wang; Yuebin Lyu; Saisai Ji; Nankun Liu; Bing Wu; Feng Zhao; Zheng Li; Yingli Qu; Yuanduo Zhu; Linna Xie; Yawei Li; Zheng Zhang; et al. (Environmental Research, 2024)

Associations of ambient air pollution with incidence and dynamic progression of atrial fibrillation - Junguo Zhang; Linna Luo; Ge Chen; Baozhuo Ai; Gan Wu; Yanhui Gao; Gregory Y.H. Lip; Hualiang Lin; Yangxin Chen (Science of The Total Environment, 2024)

TaSRT2 recognizes a viral protein to activate host immunity by increasing histone acetylation - Kaili Zhong; Yaoyao Jiang; Haichao Hu; Bowen Yuan; Mila Wu; Aizhu Tu; Gecheng Xu; Linna Cai; Tingting Liu; Shiqi Gao; Linzhi Li; Qiansheng Liao; et al. (Science Bulletin, 2024)

Impact of corticosteroid doses on prognosis of severe and critical COVID-19 patients with Omicron variant infection: a propensity score matching study - Shiyao Wang; Ziying Chen; Xinran Zhang; Xiaojing Wu; Yuqiong Wang; Qi Zhang; Linna Huang; Xiaoyang Cui; Ying Cai; Xu Huang; Jingen Xia; Sichao Gu; et al. (Inflammopharmacology, 2024)
Background There is lack of research on corticosteroid use for severe and critical COVID-19 patients with Omicron variant infection. Methods This multi-center retrospective cohort study involved 1167 patients from 59 ICUs across the mainland of China diagnosed with severe or critical SARS-CoV-2 Omicron variant infection between November 1, 2022, and February 11, 2023. Patients were segregated into two groups based on their corticosteroid treatment—usual dose (equivalent prednisone dose 30–50 mg/day) and higher dose (equivalent prednisone dose > 50 mg/day). The primary outcome was 28-day ICU mortality. Propensity score matching was used to compare outcomes between cohorts. Results After propensity score matching, 520 patients in the usual dose corticosteroid group and 260 patients in the higher dose corticosteroid group were included in the analysis, respectively. The mortality was significantly higher in the higher dose corticosteroid group (67.3%, 175/260) compared to the usual dose group (56.0%, 291/520). Logistic regression showed that higher doses of corticosteroids were significantly associated with increased mortality at 28-day (OR = 1.62,95% CI 1.19–2.21, p = 0.002) and mortality in ICU stay (OR = 1.66,95% CI 1.21–2.28, p = 0.002). Different types of corticosteroids did not affect the effect. Conclusions The study suggests that higher-dose corticosteroids may lead to a poorer prognosis for severe and critical COVID-19 patients with Omicron variant infection in the ICU. Further research is needed to determine the appropriate corticosteroid dosage for these patients.

The benzothiadiazole-based COF/CNT composite as host for efficient Li-S batteries with excellent cycling stability - Guimei Huang; Haoyu Yin; Kangkang Jia; Yuansheng Luo; Jingfu Chen; Cheng Zhong; Linna Zhu; Fei Wu (Chemical Engineering Journal, 2024)

Heavy metals and metalloids exposure and liver function in Chinese adults — A nationally representative cross-sectional study - Shiyu Wang; Yuebin Lyu; Saisai Ji; Nankun Liu; Bing Wu; Feng Zhao; Zheng Li; Yingli Qu; Yuanduo Zhu; Linna Xie; Yawei Li; Zheng Zhang; et al. (Environmental Research, 2024)

Spatiotemporal variations of non-farming use of cropland in China under different SSP-RCP scenarios - Linna Linghu; Peijun Sun; Meng Zhang; Zhangli Sun; Yue Wu (Regional Environmental Change, 2024)

Spatio-temporal evolution and topographic gradient effect of land use and ecosystem service value in the Lhasa River Basin - Jianwei Zhou; Bin Feng; Hua Wu; Tong Xu; Linna Chen; Xinyong Zhao; Qiyun Guo; Jiatong Li; Chenguang Zhang; Kangcheng Zhu; Yuzhong Kong (Journal of Mountain Science, 2024)

Paleontology Knowledge Graph for Data-Driven Discovery - Yiying Deng; Sicun Song; Junxuan Fan; Mao Luo; Le Yao; Shaochun Dong; Yukun Shi; Linna Zhang; Yue Wang; Haipeng Xu; Huiqing Xu; Yingying Zhao; et al. (Journal of Earth Science, 2024)

CiAP2/ERF65 and CiAP2/ERF106, a pair of homologous genes in pecan (Carya illinoensis), regulate plant responses during submergence in transgenic Arabidopsis thaliana - Hongxia Liu; Yangang Lan; Linna Wang; Nianqin Jiang; Xiaoyue Zhang; Min Wu; Yan Xiang (Journal of Plant Physiology, 2024)

Synthesis and application of wetland plant-based functional materials for aqueous antibiotics removal - Tao Fu; Linna Du; Suqing Wu; Min Zhao; Xiangyong Zheng; Zhiquan Wang; Yejian Zhang; Chunzhen Fan; Wen Wang; Fuyuan Ran; Ping Lin; Chunjie Zhong (Science of The Total Environment, 2024)

Genome-wide identification of the Carya illinoinensis bZIP transcription factor and the potential function of S1-bZIPs in abiotic stresses - Nianqin Jiang; Linna Wang; Yangang Lan; Hongxia Liu; Xiaoyue Zhang; Wei He; Min Wu; Hanwei Yan; Yan Xiang (Tree Genetics & Genomes, 2023)

Preparation of hypercrosslinked porous polymer with manifold functional groups for sensitive determination of phenylurea herbicides in beverages and celtuce samples - Linna Guo; Miao Tian; Zhi Li; Qianqian Wang; Qiuhua Wu; Lin Hao; Chun Wang (Food Chemistry, 2023)

Performance evaluation of resource-based city transformation: A case study of energy-enriched areas in Shaanxi, Gansu, and Ningxia - Qi Wen; Jie Fang; Linna Shi; Xinyan Wu; Anmeng Luo; Jinmei Ding (Journal of Geographical Sciences, 2023)

Genomic epidemiology of mcr carrying multidrug-resistant ST34 Salmonella enterica serovar Typhimurium in a one health context: The evolution of a global menace - Qixia Luo; Yuye Wu; Danni Bao; Linna Xu; Hangfei Chen; Meina Yue; Mohamed S. Draz; Yingying Kong; Zhi Ruan (Science of The Total Environment, 2023)

Enhancing nitrate attenuation in groundwater via selectively applying surface agricultural practices: A novel and sustainable strategy for non-point source pollution mitigation - Linna Jia; Jia Xin; Han Wu; Shuo Gong; Haoran Wu; Zhiyuan Zhang (Water Research, 2023)

Efficient degradation and decolorization of triphenylmethane dyes by Serratia sp. WKD under extreme environmental conditions and the mechanism - Linna Du; Huan Wu; Gang Li; Yi Wei; Fei Wang; Ligen Xu; Xinjiao Dong (International Biodeterioration & Biodegradation, 2023)

Research status on remediation of eutrophic water by submerged macrophytes: A review - Dongsheng Wang; Xinyu Gan; Zhiquan Wang; Shunfeng Jiang; Xiangyong Zheng; Min Zhao; Yonghua Zhang; Chunzhen Fan; Suqing Wu; Linna Du (Process Safety and Environmental Protection, 2023)

PheLBD29, an LBD transcription factor from Moso bamboo, causes leaf curvature and enhances tolerance to drought stress in transgenic Arabidopsis - Min Wu; Wei He; Linna Wang; Xiaoyue Zhang; Kang Wang; Yan Xiang (Journal of Plant Physiology, 2023)

Comparative genomic analysis of the CPK gene family in Moso bamboo (Phyllostachys edulis) and the functions of PheCPK1 in drought stress - Min Wu; Hongxia Liu; Linna Wang; Xiaoyue Zhang; Wei He; Yan Xiang (Protoplasma, 2023)

Identification and Expression Analysis of LBD Genes in Moso Bamboo (Phyllostachys edulis) - Yameng Gao; Kang Wang; Ruijia Wang; Linna Wang; Hongxia Liu; Min Wu; Yan Xiang (Journal of Plant Growth Regulation, 2022)

Identification of TCP family in moso bamboo (Phyllostachys edulis) and salt tolerance analysis of PheTCP9 in transgenic Arabidopsis - Yuzeng Xu; Linna Wang; Hongxia Liu; Wei He; Nianqin Jiang; Min Wu; Yan Xiang (Planta, 2022)

The complete mitochondrial genome of the hybrid grouper Epinephelus moara (♀)×Epinephelus tukula (♂), and phylogenetic analysis in subfamily Epinephelinae - Zhentong Li; Yongsheng Tian; Meiling Cheng; Linna Wang; Jingjing Zhang; Yuping Wu; Zunfang Pang; Wenhui Ma; Jieming Zhai (Acta Oceanologica Sinica, 2020)

Geochemical behaviors of antimony in mining-affected water environment (Southwest China) - Ling Li; Han Tu; Shui Zhang; Linna Wu; Min Wu; Yang Tang; Pan Wu (Environmental Geochemistry and Health, 2019)

Multiple parapatric pollinators have radiated across a continental fig tree displaying clinal genetic variation - Hui Yu; Enwei Tian; Linna Zheng; Xiaoxia Deng; Yufen Cheng; Lianfu Chen; Wei Wu; Wattana Tanming; Dayong Zhang; Stephen G. Compton; Finn Kjellberg (Molecular Ecology, 2019)
The ways that plant‐feeding insects have diversified are central to our understanding of terrestrial ecosystems. Obligate nursery pollination mutualisms provide highly relevant model systems of how plants and their insect associates have diversified and the over 800 species of fig trees ( Ficus ) allow comparative studies. Fig trees can have one or more pollinating fig wasp species (Agaonidae) that breed within their figs, but factors influencing their number remain to be established. In some widely distributed fig trees, the plants form populations isolated by large swathes of sea, and the different populations are pollinated by different wasp species. Other Ficus species with continuous distributions may present genetic signatures of isolation by distance, suggesting more limited pollinator dispersal, which may also facilitate pollinator speciation. We tested the hypothesis that Ficus hirta , a species for which preliminary data showed genetic isolation by distance, would support numerous pollinator species across its range. Our results show that across its range F. hirta displays clinal genetic variation and is pollinated by nine parapatric species of Valisia . This is the highest number of pollinators reported to date for any Ficus species, and it is the first demonstration of the occurrence of parapatric pollinator species on a fig host displaying continuous genetic structure. Future comparative studies across Ficus species should be able to establish the plant traits that have driven the evolution of pollinator dispersal behaviour, pollinator speciation and host plant spatial genetic structure.

Research on Rare Cranes Population Response to Land Use Change of Nature Wetland - Wenjuan Peng; Bin Dong; Shuangshuang Zhang; Hui Huang; Xiaokang Ye; Linna Chen; Qiang Zhou; Jing Wu; Cheng Wang; Ming Zhu; Kangkang Zhao; Dian Lv (Journal of the Indian Society of Remote Sensing, 2018)

Effects of mining activities on evolution of water chemistry in coal-bearing aquifers in karst region of Midwestern Guizhou, China: evidences from δ13C of dissolved inorganic carbon and δ34S of sulfate - Qingguang Li; Pan Wu; Xuefang Zha; Xuexian Li; Linna Wu; Shangyi Gu (Environmental Science and Pollution Research, 2018)

Combining multi-source data to explore a mechanism for the effects of micrometeorological elements on nutrient variations in paddy land water - Hezhen Lou; Shengtian Yang; Changsen Zhao; Zhiwei Wang; Xiaolin Liu; Liuhua Shi; Linna Wu; Fanghua Hao; Mingyong Cai (Paddy and Water Environment, 2017)

De novo transcriptome sequencing in Ficus hirta Vahl. (Moraceae) to investigate gene regulation involved in the biosynthesis of pollinator attracting volatiles - Hui Yu; John D. Nason; Lu Zhang; Linna Zheng; Wei Wu; Xuejun Ge (Tree Genetics & Genomes, 2015)

Evaluating the suitability of TRMM satellite rainfall data for hydrological simulation using a distributed hydrological model in the Weihe River catchment in China - Haigen Zhao; Shengtian Yang; Zhiwei Wang; Xu Zhou; Ya Luo; Linna Wu (Journal of Geographical Sciences, 2015)

The effect of environmental factors on spatial variability in land use change in the high-sediment region of China’s Loess Plateau - Ya Luo; Shengtian Yang; Changsen Zhao; Xiaoyan Liu; Changming Liu; Linna Wu; Haigen Zhao; Yichi Zhang (Journal of Geographical Sciences, 2014)